Efficient wound measurements using RGB and depth images. (2015) - Gaur, Akshay; Sunkara, Rithvik; Raj, Alex Noel Joseph; Celik, Turgay
This paper presents a highly portable and a cost-effective non-invasive method of finding wound measurement information using depth image from Time-of-Flight (ToF) camera and RGB image from CMOS camera. The aim of paper is to contribute towards non-contact wound measurements, by employing a cheap and readily available RGB and depth sensors as a better alternative to manual wound measurement which is performed quite predominantly even today by most of the clinicians. The application provides the user with threefold information about the wound, its depth, area and volume which are computed and displayed automatically. The user can view these parameters within a minute of capturing the pictures of the wound along with a 3D wound image. The wound depth provided to the user can be used for judging the severity of the wound or for monitoring the healing of the wound. Furthermore, our proposed method for wound measurement can be useful not only in hospitals but also for wound assessment of patients living in remote areas or those unable to visit a doctor.